MAXIMIZING THE EFFICACY OF KOOBITS: FOSTERING COLLABORATIVE LEARNING ENVIRONMENTS AND FACILITATING TEACHERS’ TECHNOLOGY INTEGRATION IN EDUCATION - Angelito Magbato Ebora (PT. Hasba Edukasi Mandiri, 2026)
This study investigates how well the digital learning platform KooBits works to improve collaborative learning in arithmetic classes in primary schools in the Philippines' Siargao division. The study uses a qualitative research approach and conducts a thematic analysis using data from focus groups, interviews, and classroom observations. The dynamics, difficulties, and advantages of using KooBits in teaching methods are revealed by this analysis. The results show that KooBits dramatically increases student zeal and engagement, turning disengaged pupils into engaged learners. This shift fosters a lifelong passion for learning in addition to improving academic performance. Moreover, KooBits fosters student collaboration by motivating even the most introverted kids to participate and communicate in the classroom. This change fosters critical abilities like communication, teamwork, and conflict resolution in a more dynamic and inclusive learning environment. The study does, however, also point out several serious difficulties, chief among them being the scarcity of essential digital tools and dependable internet connectivity. Due to the learning challenges caused by the digital divide, students may feel unfairly treated and excluded. The study also reveals a growing gap between the requirements of modern students—who are more receptive to interactive and technologically assisted instructional approaches—and traditional lecture-based methods. In summary, although KooBits successfully alters the dynamics of the classroom and student involvement, it also emphasizes the necessity of fair access to digital resources and a change to more interactive teaching approaches to meet the changing needs of today's students.